PEMBINAAN ETIKA DAN TANGGUNG JAWAB SOSIAL DALAM PEMBINAAN WARGA GEREJA MELALUI MEDIA DIGITAL DI GEREJA BETHEL INDONESIA TABGHA CABANG UPPERROOM BATAM - Suryady, Robertus; Setiawan, Eko Agus; Budiman, Ricko; Tambunan, Risky Dermawan (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The purpose of this community service is to socialize and implement ethical and social responsibility coaching in fostering church members through digital media at the Bethel Indonesia Tabgha Church, Upperroom Branch, Batam. This community service uses the methodology used in this study is a qualitative approach with descriptive analysis. Data were collected through literature studies from various sources, including books, journal articles, and relevant community service reports to gain a direct perspective on ethical and social responsibility coaching in fostering church members through digital media. The results of ethical and social responsibility coaching in fostering church members through digital media at the Bethel Indonesia Tabgha Church, Upperroom Branch, Batam, show that the integration of ethics and social responsibility in fostering church members in digital media can increase the trust and participation of the congregation, as well as have a positive impact on society. Churches that are committed to these principles will be better able to face challenges in the digital era. Therefore, it is important for churches to continue to develop an understanding and practice of ethics in all aspects of their operations, including in the use of digital media.